DEVELOPMENT OF PH-RESPONSIVE POLYMERIC MICELLES FOR TARGETED DOXORUBICIN DELIVERY TO HYPOXIC TUMOR MICRO-ENVIRONMENTS - Fathimath Saida; Jigme Dorji; David Ríos (Yayasan Adra Karima Hubbi, 2025)
Hypoxic tumor micro-environments are characterized by abnormal vascularization and acidic extracellular pH, which significantly reduce the effectiveness of conventional chemotherapy and contribute to therapeutic resistance. Doxorubicin, although widely used, suffers from severe systemic toxicity and limited selectivity toward hypoxic tumor regions. This study aims to develop pH-responsive polymeric micelles capable of selectively delivering doxorubicin to hypoxic tumor micro-environments by exploiting endogenous acidity as a biological trigger. An experimental laboratory-based design was employed involving the synthesis of amphiphilic block copolymers, micelle self-assembly, physicochemical characterization, and in vitro biological evaluation under normoxic and hypoxic conditions. Particle size, stability, drug loading, and pH-dependent release behavior were systematically assessed, followed by cytotoxicity, cellular uptake, and three-dimensional tumor spheroid studies. The developed micelles exhibited uniform nanoscale size, high encapsulation efficiency, minimal drug leakage at physiological pH, and accelerated drug release under mildly acidic conditions representative of hypoxic tumors. Enhanced intracellular doxorubicin accumulation, deeper tumor penetration, and significantly increased cytotoxicity under hypoxia were observed compared to non-responsive micelles and free drug. These findings demonstrate that pH-responsive polymeric micelles provide an effective and biologically informed platform for targeted chemotherapy in hypoxic tumor micro-environments, offering promising potential for improving therapeutic efficacy while reducing systemic toxicity.